2020
DOI: 10.48550/arxiv.2005.04097
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delay-aware Resource Allocation in Fog-assisted IoT Networks Through Reinforcement Learning

Abstract: Fog nodes in the vicinity of IoT devices are promising to provision low latency services by offloading tasks from IoT devices to them. Mobile IoT is composed by mobile IoT devices such as vehicles, wearable devices and smartphones. Owing to the time-varying channel conditions, traffic loads and computing loads, it is challenging to improve the quality of service (QoS) of mobile IoT devices. As task delay consists of both the transmission delay and computing delay, we investigate the resource allocation (i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…3) Studies on machine learning (ML)-aided IRS systems: ML [25]- [27] has shown great potentials to revolutionize communication systems [28]. Cui et al [29] developed a K-meansbased online user clustering algorithm to reduce the computational complexity and derive the optimal power allocation policy in a closed form by exploiting the successive decoding feature.…”
Section: A Prior Work 1) Studies On Irs-aided Systemsmentioning
confidence: 99%
“…3) Studies on machine learning (ML)-aided IRS systems: ML [25]- [27] has shown great potentials to revolutionize communication systems [28]. Cui et al [29] developed a K-meansbased online user clustering algorithm to reduce the computational complexity and derive the optimal power allocation policy in a closed form by exploiting the successive decoding feature.…”
Section: A Prior Work 1) Studies On Irs-aided Systemsmentioning
confidence: 99%